Orally bioavailable glutamine antagonist prodrug JHU-083 penetrates mouse brain and suppresses the growth of MYC-driven medulloblastoma()() - Hanaford, Allison R. (Transl Oncol, 2019)
A subset of poor-prognosis medulloblastoma has genomic amplification of MYC. MYC regulates glutamine metabolism in multiple cellular contexts. We modified the glutamine analog 6-diazo-5-oxo-l-norleucine (DON) to mask its carboxylate and amine functionalities, creating a prodrug termed JHU-083 with increased oral bioavailability. We hypothesized that this prodrug would kill MYC-expressing medulloblastoma. JHU-083 treatment caused decreased growth and increased apoptosis in human MYC-expressing medulloblastoma cell lines. We generated a mouse MYC-driven medulloblastoma model by transforming C57BL/6 mouse cerebellar stem and progenitor cells. When implanted into the brains of C57BL/6 mice, these cells formed large cell/anaplastic tumors that resembled aggressive medulloblastoma. A cell line derived from this model was sensitive to JHU-083 in vitro. Oral administration of JHU-038 led to the accumulation of micromolar concentrations of DON in the mouse brain. JHU-083 treatment significantly increased the survival of immune-competent animals bearing orthotopic tumors formed by the mouse cerebellar stem cell model as well as immune-deficient animals bearing orthotopic tumors formed by a human MYC-amplified medulloblastoma cell line. These data provide pre-clinical justification for the ongoing development and testing of orally bioavailable DON prodrugs for use in medulloblastoma patients.